Simulation study of wireless communication in TWDP fading - Fan, Qiaoye (Nanyang Technological University, 2023)
In wireless communication channels, the propagation of the signal can be characterized by path loss, long-term fading (shadowing) and small-scale fading. Due to the effect of multipath propagation, diffraction and scattering, the strength of the received signal changes over a short period. As a consequence, the quality of the transmitted signal is degraded and the reliability of the transmission is not guaranteed. The small-scale local fading can be statistically characterized by the popular Rayleigh-fading and Rician-fading models. The two-wave with diffuse power (TWDP) fading model has been proposed to describe certain special cases that are not able to be characterized by either Rayleigh or Rician model. The updated TWDP model depicts two specular signal components in addition to the diffused part. This dissertation encompasses a detailed investigation of the bit error rate (BER) performance of binary phase-shift keying (BPSK), differential phase-shift keying (DPSK) and frequency-shift keying (FSK) in different fading environments. The fading models include not only Rayleigh and Rician, but also TWDP with various parameters. Both the closed-form BER expressions and the simulated BER results are provided. The analysis is further extended to the diversity combining techniques such as selection combining (SC), equal-gain combining (EGC) and maximum-ratio combining (MRC). The improvements brought by these methods are evaluated and performance comparisons are made. Except for the traditional method of adding extra diversity branches, a new view of restricting total power consumed in three diversity systems is also considered in our discussion. The effect of TWDP fading on synchronous direct-sequence code division multiple access (DS-CDMA) systems is also studied through the analysis of BER and user capacity under different values of signal-to-noise ratio (SNR) and processing gain (PG).